A study for changing aspects of water polo games due to the changes in international rules in 2005 - Shimizu, N.; Takagi, H. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purpose of this study is to evaluate the aspects of the games such as swimming distance, swimming velocity and time-motion analysis under a revised condition. The activities of 18 water-polo-players (6 center forwards, 6 drivers and 6 center backs) were videotaped and analyzed, in a total of five games of the Japan Swimming Championship which was held in the Tokyo Metropolitan Gymnasium from 29th June to 1st July in 2007. As results, an average of game duration was 48min 53second. An average of swimming distance of total is 1803.3±137.8m. An average of swimming velocity of total is 0.65±0.06m/s. It is revealed that the mean duration of contact was decreased, the mean duration of swimming was increased and the mean duration of vertical position was decreased. These results show that the intention with the revision of rules has been achieved.